Symptomatic sinus bradycardia during the recovery phase of high-altitude pulmonary edema: a case report - Xie, Jiale; Li, Weiping; Luan, Jia; Cai, Zhibiao; Miao, Haijun (Frontiers in Medicine, 2026)
This case report describes a 28-year-old healthy male who developed high-altitude pulmonary edema (HAPE) after a rapid ascent. While his condition improved with standard therapy (including corticosteroids, diuretics, and supplemental oxygen), he developed symptomatic sinus bradycardia (heart rate nadir: 37 bpm) 2 days after discontinuation of these medications. The bradycardia resolved with intravenous potassium supplementation and fluid resuscitation, and his heart rate recovered to 59 bpm. This case highlights that a rebound in vagal tone and steroid withdrawal may contribute to severe bradycardia during the HAPE recovery phase, warranting heightened clinical vigilance.